Influence of Three Types of Automated Coagulometers on the International Sensitivity Index (ISI) of Rabbit, Human, and Recombinant Human Tissue Factor Preparations - Besselaar, A. M. H. P. van den; Houbouyan, L. L.; Aillaud, M. F.; Denson, K. W. E.; Johnston, M.; Kitchen, S.; Lindahl, T. L.; Marren, M.; Martinuzzo, M. E.; Droullé, C.; Tripodi, A.; Vergnes, C. (Thrombosis and Haemostasis, 1999)
Five tissue factor reagents and three types of automated instruments for prothrombin time (PT) determination were studied in an international multicenter collaborative exercise. The purpose of this work was to determine the international sensitivity index (ISI) for each combination of reagent and instrument against the international reference preparation RBT/90. Each type of instrument was used by 3 or 4 centers to assess the interlaboratory variation of the ISI. The interlaboratory variation of the ISI for each combination of reagent and instrument ranged between 0.4% and 7.8% coefficient of variation. For three reagents, the mean ISI values for ACL (nephelometric) and STA (mechanical) were practically identical, but the mean ISI values for MLA (photo-optical) were at least 10% higher. For two other reagents prepared from rabbit tissue, the mean ISI values increased in the order ACL, STA, MLA. The widest range of mean ISI values was noted with one rabbit tissue factor reagent: 1.68 for ACL and 2.00 for MLA. Exclusion of patient specimens with INR <1.5 and INR >4.5 determined by the international reference preparation resulted in a slight decrease of the mean ISI.The interlaboratory variation of the International Normalized Ratio (INR) was assessed from the results obtained with common lyophilized and deep-frozen plasmas. The use of instrument-specific ISI values resulted in reduced interlaboratory variation of the INR. It is recommended that thromboplastin manufacturers provide instrument-specific ISI values.